PENGARUH AKSESTABILITAS, KOMPETENSI, SIKAP MONETER, DAN PENGALAMAN POSITIF PENGGUNA JASA ASURANSI PRUDENTIAL DI YOGYAKARTA - Inti Dian Lisnawati (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2016)
This study was aimed to analyze the factors that influence prudential insurance purchasing decisions in Yogyakarta. The variables of this study were the acceptability of insurance conditions, competency of insurance services, monetary attitudes of consumers towards insurance, a positive experience of insurance user and insurance purchasing decisions. The population in this study was the Prudential consumers, which is located in Sleman, Kulonprogo, and Yogyakarta. The sampling technique was using Probability Sampling. The data was collected using a questionnaire. The analysis technique used was multiple linear regression with a significance level of 5%. The results showed the multiple linier regression model is Y = -0,058X1 + 0,280X2 + 0,295X3 + 0,307X4. Acceptability of insurance conditions showed no significant effect on insurance purchasing decisions. Competency of insurance services showed positive effect on insurance purchasing decisions. Monetary attitude of consumers on insurance showed positive effect on insurance purchasing decisions. Positive insurance user experience showed positive effect on insurance purchasing decisions. Keywords: acceptability of Insurance conditions, competency of insurance services, monetary attitudes of consumers towards Insurance, a positive experience of insurance user, insurance purchasing decisions